2009
DOI: 10.2174/1567270001006010114
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Analysis Rupture Index (FEARI) as an Additional Tool for Abdominal Aortic Aneurysm Rupture Prediction

Abstract: Currently, abdominal aortic aneurysms (AAAs), which are a permanent dilation of the aorta, are treated surgically when the maximum transverse diameter surpasses 5.5cm. AAA rupture occurs when the locally acting wall stress exceeds the locally acting wall strength. There is a need to review the current diameter-based criterion, and so it may be clinically useful to develop an additional tool to aid the surgical decision-making process. A Finite Element Analysis Rupture Index (FEARI) was developed.Ten patient-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Similar observations have been reported throughout numeric studies in the literature, which have shown that inflection points exhibit higher wall stresses than the maximum diameter regions. 6,11,12 Each experimental model was imaged using CT before testing to generate accurate numeric reconstructions for validation purposes using previously reported 3D reconstruction techniques and the commercially available software Mimics (Materialise). 16,23,36 Rupture occurred at the location of numerically predicted peak wall stress in 80% of cases and at high, but not peak, stress regions in 10% of cases.…”
Section: Experimental Aaa Rupture Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations have been reported throughout numeric studies in the literature, which have shown that inflection points exhibit higher wall stresses than the maximum diameter regions. 6,11,12 Each experimental model was imaged using CT before testing to generate accurate numeric reconstructions for validation purposes using previously reported 3D reconstruction techniques and the commercially available software Mimics (Materialise). 16,23,36 Rupture occurred at the location of numerically predicted peak wall stress in 80% of cases and at high, but not peak, stress regions in 10% of cases.…”
Section: Experimental Aaa Rupture Riskmentioning
confidence: 99%
“…Some interesting rupture risk parameters have recently emerged as alternatives to AAA size. AAA wall stress, 7,8 vessel asymmetry, 11 finite element analysis rupture index (FEARI), 12 rupture potential index (RPI), 9 severity parameter (SP), 10 growth of intraluminal thrombus, 18 and a method of determining AAA growth and rupture based on mathematical models 19,20 have all been proposed as useful adjuncts to AAA size, yet all require extensive validation before they can be clinically accepted. Several of these newer approaches to rupture risk rely on biomechanics and numeric models to quantify the threat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The AAA arises in the infrarenal aorta with a diameter greater than 3 cm and can be up to 9 cm in length [1,2]. Most of the studies on aneurysms have focused on already existing realistic or idealized aneurysms [33][34][35][36][37][38][39][40][41][42][43] with the aim of defining a relevant rupture criterion [4,7,10,19,20,24]. The ratio of the vessel stress to vessel strength is regarded as an alternative tool to conventional diameter criteria, which may be insufficient in small aneurysms.…”
mentioning
confidence: 99%
“…Otherwise several works attempted to implement Finite Element Methods (FEM) based simulation in the context of endovascular procedures. They were intended to deal with issues related to the understanding and the anticipation of aneurysm rupture risk, of strain, migration and endoleaks at the stent, in their pre-computed implementation [6][7][8] or to deal with catheterization simulation issues in their interactive / real time implementation 9,10 . With the extension of EVAR to more complex cases, in particular to the use of a fenestrated endograft in certain patients, the quantification of vascular deformations will become an important aspect in the planning and sizing of such devices.…”
Section: Introductionmentioning
confidence: 99%